Virulence Profiling, Multidrug Resistance and Molecular Mechanisms of Campylobacter Strains from Chicken Carcasses in Tunisia - Awatef Béjaoui; Manel Gharbi; Sarra Bitri; Dorsaf Nasraoui; Wassim Ben Aziza; Kais Ghedira; Maryem Rfaik; Linda Marzougui; Abdeljelil Ghram; Abderrazek Maaroufi (MDPI AG, 2022)
Antibiotic resistance in foodborne pathogens is an emergent global health concern. The objectives of this study were to assess antimicrobial resistance (AMR) in Campylobacter isolates from chicken carcasses and to investigate the AMR molecular mechanisms as well as the presence of virulence determinants. The study was performed on 257 samples collected from abattoirs and retail shops in northeastern Tunisia. Forty-eight Campylobacter isolates were recovered and identified as C. jejuni (n = 33) and C. coli (n = 15). Antibiotic resistance was tested against eight antibiotics and high resistance rates were observed against tetracycline (100%), erythromycin (97.9%), ciprofloxacin (73%), nalidixic acid (85.4%), ampicillin (83.3%), amoxicillin/clavulanic acid (22.9%), chloramphenicol (75%), and gentamicin (27.1%). All isolates were multidrug-resistant, and 22 resistance patterns were found. All isolates were screened for AMR genes (tet(O), tet(A), tet(B), tet(L), cmeB, ermB, blaOXA-61, and aphA-3), and for point mutations in gyrA (C257T substitution) and 23SrRNA (A2075G/A2074C) genes. All screened AMR genes, as well as the C257T and the A2075G mutations, were detected. The virulence genotypes were also determined, and all isolates carried the motility (flaA) and invasion (cadF) genes. Most of them also harbored the cdtA, cdtB, and cdtC genes, encoding the Campylobacter toxin. The screening of the cgtB and the wlaN genes, involved in Guillain-Barré Syndrome expression, revealed the presence of the cgtB in 21.2% of C. jejuni strains, whereas none of them carried the wlaN gene. Our findings highlight the emergence of Campylobacter strains simultaneously harboring several virulence and AMR determinants, which emphasizes the risk of transmission of MDR strains to humans via the food chain. Hence, controlling the dissemination of foodborne pathogens "from the farm to the fork" as well as restricting the use of antimicrobials in husbandry are mandatory to prevent the risk for consumers and to mitigate the dissemination of MDR pathogens.